2019
DOI: 10.1371/journal.pone.0208724
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic symptoms during South East Asian haze crisis are related to changes in cerebral hemodynamics

Abstract: ObjectivesForest fires in South Asia lead to widespread haze, where many healthy individuals develop psychosomatic symptoms. We investigated the effects of haze exposure on cerebral hemodynamics and new symptoms. We hypothesised that vasoactive substances present in the haze, would lead to vasodilation of cerebral vasculature, thereby altering cerebral hemodynamics, which in turn may account for new psychosomatic symptoms.MethodsSeventy-four healthy volunteers were recruited, and serial transcranial Doppler (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In a prospective study on healthy subjects with transcranial Doppler investigations conducted prior and after haze exposure, it had been found that there was a modest but significant decrease in pulsatility index (PI) and resistivity index (RI) in the left middle cerebral artery after haze exposure. Haze exposure resulted in significantly lower mean PI and RI in symptomatic subjects compared to baseline parameters, but was not significantly different in the asymptomatic subjects [21].…”
Section: Findings and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective study on healthy subjects with transcranial Doppler investigations conducted prior and after haze exposure, it had been found that there was a modest but significant decrease in pulsatility index (PI) and resistivity index (RI) in the left middle cerebral artery after haze exposure. Haze exposure resulted in significantly lower mean PI and RI in symptomatic subjects compared to baseline parameters, but was not significantly different in the asymptomatic subjects [21].…”
Section: Findings and Resultsmentioning
confidence: 99%
“…The underlying pathophysiological mechanisms for haze exposure and neurological disease remain to be concretely elucidated. However, it has been postulated that some airborne particles in the transboundary haze may have vasoactive properties when inhaled, and may lead to alterations in cerebral hemodynamics [21]. It appeared that some subjects were more susceptible to these changes than others, and that alterations in the cerebral hemodynamics were correlated with the observed neurological symptoms, such as headaches.…”
Section: Findings and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have demonstrated an association between exposure to elevated PSI levels and an increased short-term risk of mortality in Singapore. Air pollution is a tremendous public health issue, and our study has incorporated the Singapore context into the existing and growing body of evidence on the effect of air pollution on health [12,22,[52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that both long-term [2] and short-term [3][4][5] exposure to ambient air pollution impact mortality, in particular cardiovascular and respiratory mortality. Although the deleterious effects of air pollution have been demonstrated in many Western countries [6][7][8], there are fewer comparable studies conducted in Asia [9][10][11][12][13][14]. Meanwhile, air quality remains a major problem in Asian cities, with effects on cardiovascular and respiratory mortality noted in time-series data [9,15,16], along with significant public health implications [17].…”
Section: Introductionmentioning
confidence: 99%